Expertise in Setting-up Certificate Educational Programmes in Interpreting - Rebrii , Oleksandr; Pieshkova , Olha; Klimova, Diana (The Journal of V.N. Karazin Kharkiv National University. Series: Foreign Philology. Methods of Foreign Language Teaching, 2025)
The present paper concerns the implementation of the certificate educational programme ‘Conference Interpreting’ for students of the second (master’s) level of higher education at the School of Foreign Languages of V. N. Karazin Kharkiv National University. The relevance of the article is determined by: (1) the need to train interpreters to support European integration processes; (2) the desire to share the experience of the certificate programme in interpreting. The object of the study is the aforementioned certificate programme, implemented with the support of the European Parliament, and the subject of analysis is its structure, participants and conditions of implementation, advantages and disadvantages. The aim of the study is to disseminate the experience of a successful certificate programme for training interpreters at the second (master’s) level of higher education. The study was conducted using a number of methods: analysis and synthesis were used to study European requirements for the training of interpreters and to develop our own certificate programme; the descriptive method was used to describe the structure of the programme, its content and participants; the comparative method allowed us to compare the Ukrainian approach to interpreting training with the European tradition. The educational programme, worth 26 ECTS credits (780 hours), consisted of eight educational components – six practical and two theoretical ones. The programme lasted two semesters or 32 weeks. The total number of classroom hours was 256, with a weekly workload of 8 hours (6 practical and 2 lecture hours). The online implementation of the programme had its advantages: (1) the opportunity to obtain additional qualifications in free time outside of the main course; (2) the availability of online tools for practising all types of interpreting skills; (3) the spread of remote interpreting. Based on our own experience, we have formulated a number of recommendations for the organisation of similar programmes by other higher education institutions in Ukraine.